The influence of Image and Service Value on Mobile Banking Loyalty - Fragata, Anabela (Archives of Business Research, 2019)
This paper intends to empirically examine the impact of Image and Service Value on Mobile Banking Services Loyalty. The data was analysed by employing exploratory as well as confirmatory analysis and a Structural Equation Model was extracted from 120 Portuguese respondents. The results suggest that Image and Service Value are positively related with Mobile Banking Loyalty. We also found a strong impact of Image on the Perceived Service Value.